SISTEM PERTANGGUNGJAWABAN PIDANA PADA TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA - Titik Suharti (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
System of code penal responsibility at crime hardness in house hold, has arranged UU No. 23 Th. 2004. it’s scope: physicall hardness, psychological hardness, sex hardness and it’s let house hold.